Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/j.1365-2966.2011.19743.x
|View full text |Cite
|
Sign up to set email alerts
|

Observational constraints on the model parameters of a class of emergent universe

Abstract: A class of emergent universe models is studied in the light of recent observational data. Significant constraints on model parameters are obtained from these observations. The density parameter for a class of models is also evaluated. Some of the models are in accordance with recent observations. Others are not of interest, yielding unrealistic present‐day values of the density parameter.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The presence of such a pre-inflationary phase in the EU scenario has observable consequences, namely on the anisotropies within the CMB spectrum at large scales, see e.g., [161][162][163]. Utilizing the recently developed state-finder parameters, the behavior of different stages of the evolution of the EU model has been studied and it is shown that the universe starts from an asymptotic ES state and goes to the CDM model [66] (for a systematic analysis of EU scenario, its transition to slow-roll inflation through a period of super-inflationary regime, see [164][165][166] and the references therein). In the current study, we observed that the equilibrium point for case iii could be stable or unstable depending on the value of w parameter.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of such a pre-inflationary phase in the EU scenario has observable consequences, namely on the anisotropies within the CMB spectrum at large scales, see e.g., [161][162][163]. Utilizing the recently developed state-finder parameters, the behavior of different stages of the evolution of the EU model has been studied and it is shown that the universe starts from an asymptotic ES state and goes to the CDM model [66] (for a systematic analysis of EU scenario, its transition to slow-roll inflation through a period of super-inflationary regime, see [164][165][166] and the references therein). In the current study, we observed that the equilibrium point for case iii could be stable or unstable depending on the value of w parameter.…”
Section: Discussionmentioning
confidence: 99%
“…During the SDSS survey spectroscopic samples were retrieved from thousands of red galaxies that spanned across the sky, covering a diameter of around five billion light yeras. The BAO peak parameter is defined as (Thakur, Ghose & Paul 2009;Paul, Thakur & Ghose 2010;Paul, Ghose & Thakur 2011;Ghose, Thakur & Paul 2012):…”
Section: B Joint Analysis With Cc+baomentioning
confidence: 99%
“…(Wu & Yu 2007;Thakur, Ghose & Paul 2009;Paul, Thakur & Ghose 2010;Paul, Ghose & Thakur 2011;Ghose, Thakur & Paul 2012) …”
mentioning
confidence: 99%
“…This model (2.1) can produce a emergent universe without the time singularity [43][44][45][46]. But in this paper, we will take this RMCG fluid as the dark components in our Universe.…”
Section: Dark Models In Rmcg Cosmologymentioning
confidence: 99%